2015
DOI: 10.1002/mc.22347
|View full text |Cite
|
Sign up to set email alerts
|

Cavin‐2 in oral cancer: A potential predictor for tumor progression

Abstract: Cavin-2 (CVN2) affects formation of large caveolae, which are membrane-rich cholesterol domains associated with several functions in signal transduction. Accumulating evidence suggests that CVN2 is present in many cellular types; however, the molecular mechanisms of CVN2 in cancers and its clinical relevance are unknown. We proposed a mechanism by which CVN2 regulates caveolin-1 expression leading to slow cellular proliferation by inactivation of the extracellular regulated kinase (ERK) pathway. Quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Given the recognized contribution of MSC within (patho)physiological settings is currently of great interest towards either their therapeutic applications or as intermediates in solid tumour development, the dual roles of Caveolins and of Cavins must be better documented. Our study defines Cavin-2 as a putative suppressor regulator in TNF-mediated pro-inflammatory and pro-angiogenic conditions, and supports the recent evidence found in OSCC where its down-regulation was functionally and clinically linked to tumoural progression (36). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given the recognized contribution of MSC within (patho)physiological settings is currently of great interest towards either their therapeutic applications or as intermediates in solid tumour development, the dual roles of Caveolins and of Cavins must be better documented. Our study defines Cavin-2 as a putative suppressor regulator in TNF-mediated pro-inflammatory and pro-angiogenic conditions, and supports the recent evidence found in OSCC where its down-regulation was functionally and clinically linked to tumoural progression (36). …”
Section: Discussionsupporting
confidence: 90%
“…Cavin-2 was recently suggested to regulate Caveolin-1 expression, leading to slow oral squamous cell carcinoma (OSCC) proliferation by inactivation of the extracellular regulated kinase (ERK) pathway (36). Cavin-2 may therefore be a possible key regulator of OSCC progression via a Cavin-2/Caveolin-1/ERK pathway and a potential therapeutic target for developing new treatments for OSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Cavins play important roles in caveolae biogenesis, regulating caveolar function and organization [31]. Evidence showed that cavin-2 (serum deprivation protein response, SDPR) was present in many cellular types, and down-regulated in several different cancers including breast, gastric, kidney, prostate and oral cancer [28,32]. In 2016, Ozturk et al [27] found that cavin-2 could be a potential prognostic biomarker and a therapeutic target for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, researchers suggested that transforming growth factor-β (TGF-β), which can induce EMT, was blocked by cavin-2 in breast cancer. In oral squamous cell carcinomas, Unozawa et al [32] suggested that the ERK signaling pathway was attenuated frequently in the overexpression cavin-2 cells. In studied cancers, cavin-2 was a metastasis suppressor by inhibiting EMT, migration, and intravasation accompanied with promotion of apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentration was measured using a commercial Bradford reagent (Bio-Rad Laboratories, Inc., Hercules, CA, USA). Immunoblot analysis was performed as described previously (14,(34)(35)(36)(37). Briefly, protein extracts (20 µg) were electrophoresed on 4-12% Bis-Tris gel (Invitrogen; Thermo Fisher Scientific, Inc.), transferred to polyvinylidene fluoride membranes (Invitrogen; Thermo Fisher Scientific, Inc.), and blocked for 1 h at room temperature in Blocking One (Nacalai Tesque Inc., Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%